FACTORS INFLUENCING EMPLOYEE PERFORMANCE IN THE CONDITIONS OF ENFORCED REMOTE WORKING: THE EMPLOYEE EXPERIENCE PERSPECTIVE - Gołembski, Marcin; Skowron - Mielnik, Beata; Wojtkowiak, Grzegorz (Organizacja i Kierowanie, 2025)
The aim of this paper is to identify, classify and evaluate the determinants of employee performance and team functioning in enforced remote working and, presently, in the conditions of remote and hybrid work. The empirical part includes the results of a diagnostic survey conducted on a sample of 500 employees in international corporations who had not previously worked remotely. Statistical analyses were performed to identify correlations and systemize the data obtained in the study. The discussion presented in this paper leads to the general conclusion that the COVID-19 pandemic affected the situation in enterprises in two fundamental ways. Firstly, it exposed weaknesses and deficits in management systems, manifested primarily by limited adaptability and, as a result, a lack of broadly defined flexibility. Secondly, the phenomenon of enforced remote working, discussed in the paper, inspired completely new directions in the design and organization of work processes and workplaces. The study results presented in this paper open up the field for further research, which may contribute to management theory and have practical. The first challenge for researchers is to redefine, both in theory and practice, the concepts of ‘workplace’ and ‘job’. The second important research problem, building on the observations discussed in this article, is to answer the question about the tools that could help managers adjust their management methods to the factors identified in our study.